70 years on ’the Freedom Charter is not irrelevant - it is unfinished’ - Sitas, Ari (New Agenda: SA Journal of Social and Economic Policy, 2025)
When the Freedom Charter was adopted in 1955 in Kliptown, it was more than a political manifesto — it was a transformative social contract drafted, as Congress leadership claimed, by ordinary South Africans from all walks of life. Here, Ben Turok, the founder of this Institute, had a big task in collating the material gathered from many working groups on the “ground.” The two economic clauses—“The People Shall Share in the Country’s Wealth” and “There Shall Be Work and Security”—were particularly powerful because they addressed not only political exclusion under apartheid, but the deep economic dispossession that had long defined black life in South Africa.